2013
DOI: 10.1159/000351049
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Dominant Polycystic Kidney Disease: Prevalence of Renal Neoplasias in Surgical Kidney Specimens

Abstract: Background: The role of autosomal dominant polycystic kidney disease (ADPKD) as a risk factor for renal cell carcinoma (RCC) is still under discussion. Data on prevalence of RCC in ADPKD are limited, especially on a large population scale. The aim of this study was to analyze the prevalence of RCC in ADPKD kidneys and characterize the clinical features of this coincidence. Methods: Based on our histopathological registry for ADPKD and the Else Kröner-Fresenius Registry, we retrospectively reviewed malignant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 38 publications
0
56
0
1
Order By: Relevance
“…42 Yet, in PKD, numerous studies have shown that very little RCC is seen 43 unless the kidneys are removed and examined histologically. 44,45 This very low level of diagnosed RCC in ADPKD suggested that there may be a degree of protection from cancer associated with PKD mutations. As such, we carried out an epidemiologic study to answer this question.…”
Section: Neoplastic Cyst Growth-but Why Not Cancer?mentioning
confidence: 99%
“…42 Yet, in PKD, numerous studies have shown that very little RCC is seen 43 unless the kidneys are removed and examined histologically. 44,45 This very low level of diagnosed RCC in ADPKD suggested that there may be a degree of protection from cancer associated with PKD mutations. As such, we carried out an epidemiologic study to answer this question.…”
Section: Neoplastic Cyst Growth-but Why Not Cancer?mentioning
confidence: 99%
“…7,8 This cyst formation is associated with cellular dedifferentiation and is considered a neoplastic process driven by upregulated proto-oncogenes. [9][10][11][12][13] While published case reports document the occurrence of renal cell carcinomas (RCCs) in ADPKD-affected kidneys, 14,15 these tumors may be partly due to acquired renal cystic disease resulting from long-term dialysis. 16 Because there do not appear to be widespread published reports of other cancers in patients with ADPKD, protective mechanisms might exist in ADPKD to prevent malignant transformation.…”
mentioning
confidence: 99%
“…This has been also mentioned as an indication of native nephrectomy. 52,53 In our study, one-fifth of the patients in the deceased-donor group and one-fifth of the patients in the living-donor group underwent native nephrectomy. There was no significant difference between the groups regarding the time of nephrectomy, with most of the nephrectomies that did not occur simultaneously performed unilaterally before kidney transplant.…”
Section: Abbreviations: Ns Not Significantmentioning
confidence: 73%